ANALISIS KEBUTUHAN PEREKAM MEDIS BAGIAN PENDAFTARAAN BERDASARKAN BEBAN KERJA: LITERATURE REVIEW - Nauri Anggita Temesvari; Ryo Hikmah Tiyardi (Program Studi Perekam Medis & Informasi Kesehatan, 2021)
The medical recorders at the registration site have an important role because the initial documentation of the patient begins in the registration process. In general, the registration place can be divided into outpatient, inpatient, and emergency patient registration places. Several studies have shown the obstacles experienced by the medical recorders in the registration section, including queues, the medical record documents were not found, and the patient did not carry an identity card for treatment. From these problems, the purpose of this study is to analyze the need for medical recorders in the registration section based on the workload in the literature review. The design of this research is a literature review. The article in this study uses a time span of the last 5 years (2014 - 2019) and focuses on the area of research conducted in the hospital. Furthermore, from the screening results according to the inclusion and exclusion criteria of research articles, 6 research articles were obtained. The results of the review of the article show that the average available work time is 2,156 hours/year, the average standard time workload is 215,595 minutes/year, the average allowance standard is 0.15, and the need for available medical recorders that has been met is 34%. From the results of the research, there were still those that did not meet the need for medical recorders because they did work outside their basic duties. In addition, the process of searching for medical records that hampers services raised queuing problems.